Diabetic Muscle Infarction of the Tibialis Anterior and Extensor Hallucis Longus Muscles Mimicking the Malignant Soft-Tissue Tumor - Yoshikuni Mimata; Kotaro Sato; Karen Tokunaga; Itsuko Tsukimura; Hiroshi Tada; Minoru Doita (Case Reports in Orthopedics)
One of the most common causes of skeletal muscle infarction is diabetic muscle infarction (DMI), a rare complication associated with poorly controlled diabetes. We report an atypical case of DMI localized in the tibialis anterior (TA) and extensor hallucis longus (EHL) muscles of an elderly individual. A 64-year-old man with type 2 diabetes mellitus presented with a 6-month history of a palpable mass in his lower left leg. Magnetic resonance imaging (MRI) revealed that the mass exhibited heterogeneous signals on T1- and T2-weighted images and slight heterogeneous enhancement within the muscles on fat suppressed T1-weighted images. Because histopathological analysis revealed mostly necrotic muscle tissues but no neoplastic cells, we resected the affected muscles. A typical symptom of DMI is severe abrupt-onset pain in the region of the affected muscles, but the patient did not complain of pain. Therefore, the diagnosis and treatment for DMI were delayed, and widespread irreversible muscle necrosis developed. MRI findings of DMI can be similar to that of a malignant soft-tissue tumor. So, it is necessary to consider the malignant soft-tissue tumor as one of the differential diagnoses of DMI.